2015
DOI: 10.1111/apa.13014
|View full text |Cite
|
Sign up to set email alerts
|

More training and awareness are needed to improve the recognition of undernutrition in hospitalised children

Abstract: Half of the paediatric departments in Belgian secondary-level hospitals did not carry out nutritional screening, and differences in current practices and attitudes may be due to cultural and/or educational differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Low staff awareness on nutrition, lack of time and lack of local guidelines for nutrition screening were the most important barriers to the routine evaluation of DAM. These results are very similar to the findings of a Belgian survey in secondary care hospitals 14 . The differences across countries in the perceived barriers of routine evaluation of DAM may reflect variation in health practices, resources and agreed health priorities across countries.…”
Section: Discussionsupporting
confidence: 90%
“…Low staff awareness on nutrition, lack of time and lack of local guidelines for nutrition screening were the most important barriers to the routine evaluation of DAM. These results are very similar to the findings of a Belgian survey in secondary care hospitals 14 . The differences across countries in the perceived barriers of routine evaluation of DAM may reflect variation in health practices, resources and agreed health priorities across countries.…”
Section: Discussionsupporting
confidence: 90%
“…Median (interquartile range, IQR) LOS was also longer in acutely malnourished children than in those not acutely malnourished (17.5 days, 12–58 vs. 5 days, 2–13, respectively), ( p = 0.051). The LOS for those whose height SD was below and above − 2 SD was 14 days (4–121) and 4.5 days [212], respectively ( p = 0.090). Age of the child did not differ between malnourished or well-nourished groups or between the risk scores of any of the screening methods.…”
Section: Resultsmentioning
confidence: 99%
“…Malnutrition is an underrecognized problem leading to an increased risk for complications, longer hospital stays, and decreased quality of life [1, 2]. Several guidelines suggest that pediatric hospital inpatients should be screened for malnutrition risk [3].…”
Section: Introductionmentioning
confidence: 99%
“…Serum albumin and pre-albumin are routinely used in clinical practice as biochemical indicators of nutritional status. In a national survey published in 2015, we reported that more than one-third of Belgian paediatric departments considered serum protein levels in their nutritional assessment (1). However, both serum markers were said to be unreliable nutritional indicators in calorically restricted individuals without physical illness in a systematic review, which contained mainly adult data and a combination of different small studies in adolescents (2).…”
Section: Introductionmentioning
confidence: 99%